Proceedings of Cycad 2008 : the 8th International Conference on Cycad Biology : 13-15 january 2008, Panama City, Panama - Stevenson, Dennis Wm., 1942-; Osborne, Roy; Taylor Blake, Alberto Sidney, 1932- ((Memoirs of the New York Botanical Garden ;, 2012)
Cycads have been around since the Late Permian. During this time they have retained seemingly unchanged features, yet they have evolved unique characteristics that science continues to uncover. As the discoveries keep coming, medicine and agriculture find new applications for what cycads have to offer, lending to their status as an irreplaceable group within the world's diverse plant kingdom. The International Conference on Cycad Biology, held every three years since its inception in 1987, is a prominent meeting centering on all aspects of the biology of this unusual, important, and interesting group of plants. The conference stimulates research in fields as diverse as horticulture and neurobiology; it also promotes ex-situ and in-situ conservation globally. Each conference has produced a volume of papers on the varied aspects of cycad biology. This volume, the eighth of its kind, is the most extensive to date. It represents the current state of knowledge about the evolution, pollination biology, ethnobotany, conservation status, and molecular biology of the living cycads. Some articles are in Spanish; every article has an abstract in English and Spanish. Having survived for 250 million years, cycads now find themselves endangered as a result of human activity. This volume addresses the issue from angles that include conservation biology, pest control, the role of insects and birds in cycad biology, and the role of cycads in various human cultural contexts.